Recent Updates on Acetaminophen Hepatotoxicity: The Role of Nrf2 in Hepatoprotection - Gum, Sang Il (The Korean Society of Toxicology, 2013)
Acetaminophen (APAP) known as paracetamol is the main ingredient in Tylenol, which has analgesic and anti-pyretic properties. Inappropriate use of APAP causes major morbidity and mortality secondary to hepatic failure. Overdose of APAP depletes the hepatic glutathione (GSH) rapidly, and the metabolic intermediate leads to hepatocellular death. This article reviews the mechanisms of hepatotoxicity and provides an overview of current research studies. Pharmacokinetics including metabolism (activation and detoxification), subsequent transport (efflux)-facilitating excretion, and some other aspects related to toxicity are discussed. Nuclear factor erythroid 2-related factor 2 (Nrf2)-regulated gene battery plays a critical role in the multiple steps associated with the mitigation of APAP toxicity. The role of Nrf2 as a protective target is described, and potential natural products inhibiting APAP toxicity are outlined. This review provides an update on the mechanism of APAP toxicity and highlights the beneficial role of Nrf2 and specific natural products in hepatoprotection.